In vitro antimicrobial activity of crude extracts of Jatropha species - Gaikwad, Rajesh S; Kakde, Rajendra B; Kulkarni, Anil U; Gaikwad, Deepmala R; Panchal, V H (Current Botany, 2012)
Leaf extracts, stem extract, roots extract, latex and oil of Jatropha curcas, J. glandulufera, J. integerrima and J. gossypofolia were screened in order to study their effect on plant pathogenic fungi Alternaria alternata, Aspergillus flavus, Aspergillus niger, Fusarium oxysporum, and Rhizoctonia solani and plant pathogenic bacteria Erwinia carotovora pv. Carotovora, Pseudomonas aeruginosa, Xanthomonas campestris pv. Citri and Xanthomonas campestris pv. mangiferaeindicae. Degree of variation of antifungal and antibacterial activity of different parts of Jatropha sp. was observed.